The Determining Ko Atek’s Cakue Packaging Concept through Kansei Engineering Methodology - Sari, Novi Purnama; Wicaksono, Dimas Priyo; Aristanti, Khairunnisa; Slamet, Sesar Chairudin (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
Cakue Ko Atek is one of the culinary MSMEs in Jakarta that has been famous since 1971 until now. Cakue Ko Atek products have faced several challenges, especially in the packaging aspect, which still has many shortcomings, namely not having a clear product identity, using recycled paper, and being packaged with plastic, making it less attractive to consumers and having an impact on the environment. This packaging development research aims to formulate a new packaging design concept that is more aesthetic and functional but meets consumer expectations and desires. To achieve this goal, the Kansei Engineering method was applied in the process of determining the packaging concept with the aim of understanding and interpreting consumer perceptions of the ideal packaging design. The collected consumer perception data are then processed with the Principal Component Analysis (PCA) method to simplify the Kansei word data and find the main components in consumer perceptions. The analysis was conducted using R software to identify relevant key design concepts based on PCA. The results of this analysis showed that there was one Principal Component (PC) with the highest standard deviation in PC 1, which amounted to 6.686, which became the basis for formulating the design concept. The resulting design concept, based on the positive and negative quadrant analysis data on PC 1, is Usable-Simple, which reflects consumer needs for packaging that is easy to use and has a simple yet effective appearance. This research only produces design concepts that are in accordance with consumer preferences and has not evaluated specific design elements that can be implemented on packaging based on the concepts that have been formulated.